2013
DOI: 10.7150/ijms.7087
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Radial Artery Occlusion Associated Transradial Catheterization

Abstract: In this study, we sought to assess the incidence and predictors of radial artery occlusion (RAO), which is a significant complication of transradial cardiac catheterization. We prospectively evaluated the results of 106 patients who underwent coronary angiography and percutaneous coronary intervention (PCI) via the transradial approach (TRA). At the 3rd h of intervention, the radial artery was checked by palpation; color doppler ultrasonography was performed at the 24th h. Fluoroscopy duration, procedure succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
0
23
0
3
Order By: Relevance
“…29,49,69,73,77,78 Body weight was reported as a significant predictor in 3 studies. 17,65,75 In terms of procedural variables, use of a smaller introducer sheath has been shown to be predictive of lower RAO 71 and use of larger diameter of sheath 42,78,81 and duration of compression 61,81 was associated with higher occlusion rates. Other predictors included baseline radial artery diameter, 19,84,85 peripheral artery disease, 79 statin use, 42 procedural success, 47 serum creatinine, 49 and heparin use.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29,49,69,73,77,78 Body weight was reported as a significant predictor in 3 studies. 17,65,75 In terms of procedural variables, use of a smaller introducer sheath has been shown to be predictive of lower RAO 71 and use of larger diameter of sheath 42,78,81 and duration of compression 61,81 was associated with higher occlusion rates. Other predictors included baseline radial artery diameter, 19,84,85 peripheral artery disease, 79 statin use, 42 procedural success, 47 serum creatinine, 49 and heparin use.…”
Section: Resultsmentioning
confidence: 99%
“…Age was reported to be a significant predictor of RAO in 3 studies, while sex was significant in 6 studies . Body weight was reported as a significant predictor in 3 studies . In terms of procedural variables, use of a smaller introducer sheath has been shown to be predictive of lower RAO and use of larger diameter of sheath and duration of compression was associated with higher occlusion rates.…”
Section: Resultsmentioning
confidence: 99%
“…26 In another study radial artery diameter and vasodilatory properties were assessed by high resolution ultrasound at 10 to 14 months after TCC and found that radial artery diameter was reduced while vasodilatory properties were preserved. 27 The only case of RAO in our study was a female and the reduction of mean radial artery diameter after TCC was significantly more in female (p=0.032).…”
Section: Discussionmentioning
confidence: 99%
“…The complications described herein—permanent ischemic damage and pseudoaneurysm—are very rare adverse effects, with rates of 0.09% each [ 1 ]. Risk factors for complications involve the cannula size, vasospasm, patient age, female sex, high number of puncture attempts, and duration of catheter placement [ 5 - 8 ].…”
Section: Discussionmentioning
confidence: 99%